OP0053 Eular/ERA-EDTA Recommendations for The Management of Anca-Associated Vasculitis. (15th July 2016) - Yates, M.; Watts, R.; Bajema, I.; Cid, M.; Crestani, B.; Hauser, T.; Hellmich, B.; Holle, J.; Laudien, M.; Little, M.; Luqmani, R.; Mahr, A.; et al.
Abstract : Background: The European League Against Rheumatism (EULAR) Recommendation for primary and small vessel vasculitis were published in 2009. Objectives: To update the 2009 recommendations with the focus being ANCA-Associated Vasculitis (AAV) using systematic literature review, as well as expert opinion where appropriate. Methods: A combined taskforce from European League Against Rheumatism (EULAR), the European Renal Association (ERA-EDTA) and European Vasculitis Society (EUVAS) conducted a modified Delphi exercise to identify key areas of guideline for update. The identified themes were then used to generate keywords for literature searches. For the purpose of update a date period of 1st January 2007 to 1st February 2015 was chosen, to interrogate the main medical literature databases (MEDLINE, EMBASE, CENTRAL). From an initial 1, 347 hits, 82 clinically relevant studies were identified. The evidence presented was discussed and summarized by the experts in the course of a consensus finding and voting process. Levels of evidence and grades of recommendations were derived and levels of agreement (strengths of recommendations) were determined. Results: The 15 recommendations cover general aspects, such as attainment of remission and the need for shared decision-making between rheumatologists and patients. The more specific items relate to starting immunosuppressive therapy using a strategy in combination with glucocorticoids to induce remission, followed by a period of remission maintenance. For remission induction of life or organ-threatening AAV, cyclophosphamide and rituximab are considered to have similar efficacy. Azathioprine, rituximab and methotrexate are the preferred choices for remission maintenance. The recommendations address plasma exchange which is recommended, in the setting of rapidly progressive renal failure or severe diffuse pulmonary haemorrhage. To enable the recommendations to have maximum validity the voting process was also repeated amongst the members of EUVAS. Conclusions: The recommendations have been updated and changes include; choice of drug therapy (both for induction, relapse and remission maintenance), monitoring for complications, the usefulness of repeated biopsy in those thought to having relapsing disease, monitoring for hypoimmunoglobulinaemia and recommendations on patient education. These recommendations are intended for use by healthcare professionals, doctors in specialist training, medical students, pharmaceutical industries and drug regulatory organisations. Disclosure of Interest: None declared